Textural evaluation of sausages as affected by partial meat substitution using okara tempe - Ramadhan, Kurnia; Eka Rada, Febriana; Asiah, Nurul; Cempaka, Laras (Asia Pacific Network for Sustainable Agriculture, Food and Energy Network (SAFE Network), 2022)
Okara tempe has been traditionally consumed as low-cost meat substitute. This study aims to evaluate the textural properties of sausage as affected by partial meat substitution using okara tempe. Two types of sausages were tested, namely cellulose-cased and collagen-cased sausages with the level of meat substitution at 0, 10, and 20 %. The scope of assessment includes texture profile analysis, scanning electron microscopy, and sensory evaluation. The results showed that increasing okara tempe concentration led to a decreasing hardness and resilience of sausage samples. Microscopy images revealed fractal structure on the inner surface of okara tempe-substituted sausages that might be responsible for weakening of the structure. Consumers’ appreciation on sausage texture tended to be decreased with the increasing concentration of okara tempe. Agglomerative hierarchical clustering analysis distributed the consumer panels into two clusters with slightly different hedonic scoring pattern. Lastly, although the okara tempe-substituted sausages had a weaker structure, the means of hedonic scores of all sausage samples were within positive response range indicating consumers’ acceptance to the okara tempe-substituted sausages.